Enterovirus 71 Infection Induces Apoptosis in Vero Cells - Chan, Y.F.; AbuBakar, Sazaly (2003)
The effects of Enterovirus 71 (HEV71) infection on African green monkey kidney cells (Vero) were investigated. It was found that the infected cells showed progressive cellular morphological changes characteristic in apoptotic cells within 10 hours post-infection. The number of apoptotic cells correlated significantly with the number of HEV71 antigen positive cells when cells were labeled using terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labeling (TUNEL) and stained for HEV71 antigen. Approximately 11, 26, 45 and 50 of the infected cells were apoptotic at 12, 24, 48 and 72 hours post-infection, respectively. Internucleosomal DNA fragmentation, characteristic in the late stage of apoptosis was noted beginning on day 2 post-infection. The DNA fragmentation, however, was absent in cells treated with the heat- and ultraviolet light-inactivated virus inocula. These results demonstrate the capacity of HEV71 to induce apoptosis in the infected cells. The induction, however, requires high level of HEV71 infectivity and the presence of live virus particles, suggesting the need for the presence of specific viral proteins for apoptosis to occur.